Design and Fabrication of Hydraulic Scissor Lift Platform. - Muhindo, Boneface (Kabale University, 2023)
Scissor lifting machine is hydraulically operated with makes lifting simple by eluding bending onward to lift manually because the table is regulating to be lifted at a preferred height. There are predominantly hundreds of workers for lift tables in industrial, warehousing and delivery services. The addition of this device (lift table) makes job quicker, harmless and easier. The overall objective of this paper is to design and fabricate a double scissors lift device elevated by one hydraulic cylinder that can be used in the automobile garages, industry, warehouses. The machine is tested by lifting different weights and it is successful and can lift up to the recommended weight of 300kg efficiently without any problem. Drafting & drawing of hydraulic system scissor lift is done using solid works.